Spontaneous contractions of the human thoracic duct—Important for securing lymphatic return during positive pressure ventilation?. Issue 10 (17th May 2022) - Kelly, Benjamin; Smith, Christopher L.; Saravanan, Madhumitha; Dori, Yoav; Hjortdal, Vibeke E.
Abstract: The thoracic duct is responsible for the circulatory return of most lymphatic fluid. The return is a well‐timed synergy between the pressure in the thoracic duct, venous pressure at the thoracic duct outlet, and intrathoracic pressures during respiration. However, little is known about the forces determining thoracic duct pressure and how these respond to mechanical ventilation. We aimed to assess human thoracic duct pressure and identify elements affecting it during positive pressure ventilation and a brief ventilatory pause. The study examined pressures of 35 patients with severe congenital heart defects undergoing lymphatic interventions. Thoracic duct pressure and central venous pressure were measured in 25 patients during mechanical ventilation and in ten patients during both ventilation and a short pause in ventilation. TD contractions, mechanical ventilation, and arterial pulsations influenced the thoracic duct pressure. The mean pressure of the thoracic duct was 16 ± 5 mmHg. The frequency of the contractions was 5 ± 1 min −1 resulting in an average increase in pressure of 4 ± 4 mmHg. During mechanical ventilation, the thoracic duct pressure correlated closely to the central venous pressure. TD contractions were able to increase thoracic duct pressure by 25%. With thoracic duct pressure correlating closely to the central venous pressure, this intrinsic force may be an important factor in securing a successful return of lymphatic fluid. Future studies are needed to examine the return of lymphatic fluid and the function of the thoracic duct in the absence of both lymphatic complications and mechanical ventilation. Abstract : In individuals with congenital heart defects undergoing lymphatic interventions, thoracic duct pressure correlates closely to central venous pressure. The thoracic duct spontaneously contracts with a frequency of 5 min −1 increasing thoracic duct pressure by 25%. Spontaneous contractions of the thoracic duct may be an important factor in securing the successful return of lymphatic fluid when challenged by positive pressure ventilation.